Characterization of EDFA by Using Different Measurement Methods - T.C, Teyo; M.K, Leong; Shah N.S, Mohd.; P, Poopalan; S.W, Harun; H, Ahmad H (Malaysian Journal of Science, 2003)
Different methods for conventional erbium-doped fiber amplifier (EDFA) evaluation, namely Interpolation Method and Time-Domain Extinction (TDE) or Pulsed Method are compared. Principles of both measurement methods are also addressed. The data showed that discrepancies in signal gain and noise figure rose from different ways in the determination of the amplified spontaneous emission (ASE) level.